Water reuse and aquaculture: Pharmaceutical bioaccumulation by fish during tertiary treatment in a wastewater stabilization pond - Grabicová, Kateřina; Grabic, Roman; Fedorova, Ganna; Vojs Staňová, Andrea; Bláha, Martin; Randák, Tomáš; Brooks, Bryan W; Žlábek, Vladimír (Environmental pollution (Barking, Essex, 2020)
With increasing demand for aquaculture products, water reuse is likely to increase for aquaculture operations around the world. Herein, wastewater stabilization ponds (WSP) represents low cost and sustainable treatment technologies to reduce nutrients and various contaminants of emerging concern from effluent. In the present study, we examined bioaccumulation of selected pharmaceuticals from several therapeutic classes by two important fish species in aquaculture with different feeding preferences (Cyprinus carpio and Sander lucioperca) and their common prey to test whether species specific accumulation occurs. Forty and nineteen from 66 selected pharmaceuticals and their metabolites were positively found in water and sediment samples, respectively from the representative WSP. After a six-month study, which corresponds to aquaculture operations, fourteen pharmaceuticals and their metabolites were detected (at a frequency of higher than 50% of samples) in at least one fish tissue collected from the WSP. We observed striking differences for species and organ specific BAFs among study compounds. Though muscle tissues consistently accumulated lower levels of the target analytes, several substances were elevated in brain, liver and kidney tissues (e.g., sertraline) of both species. Low residual concentrations of these target analytes in aquaculture products (fish fillets) suggest WSPs are promising to support the water-food nexus in aquaculture.
Keywords: Ponds; Waste Water; odpadní voda; voda; Aquaculture; Bioaccumulation; kapři; Water; Pikeperch; rybníky; chemické látky znečišťující vodu; Carps; Water Pollutants, Chemical; léčivé přípravky; zvířata; Wastewater; Contamination; Pharmaceutical Preparations; Common carp; vodní hospodářství; Treated wastewater; bioakumulace; Animals